The metamorphosis of biographical novel genre in the creativity of peter ackroyd (Eurasian Journal of Philology Science and Education, 2018)
Ackroyd ‘s creativity who brought new metamorphosis to biographical novel genre of the twentieth century is interesting in several aspects. Author approachs biographical novel from the standpoint of tradition and innovator problems. In his novels Ackroyd not only preserved historicity and documentary but also achieved historical parody, ironic and fantastic rivets and thus, has changed the content and form of biographical novel genre.
Keywords: biographical novel; Peter Ackroyd; psychogeographic portrait.